Produkcja włókiennicza we wschodniej części Dolnych Łużyc w okresie industrialnym. Zagadnienia społeczno-gospodarcze = Textile industry in the east part of Lower Lusatia during the Industrial Period. Social and economic issues - Partyka, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Weaving was one of the most popular occupations in Lower Lusatia during the period when hand loom weavers started to be replaced by power loom weavers. The subject of social and economic issues is so vast that it has been divided into two parts.In the first part there is the analysis of the employment status of craftsmen and factory workers, as well as vocational education, social issues and the general characteristics of the textile industry in the region from 1815, when the Lower Lusatia was incorporated into Prussia, until the outbreak of the Second World War.
Keywords: włókiennictwo; Dolne Łużyce; industrializm; textiles; Lower Lusatia; industrialism